2016
DOI: 10.1590/0103-8478cr20150505
|View full text |Cite
|
Sign up to set email alerts
|

Replacing sugar with S. rebaudiana extracts on the physicochemical and sensory properties of strawberry ice cream

Abstract: Replacing sugar with S. rebaudiana extracts on the physicochemical and sensory properties of strawberry ice cream.Ciência Rural, v.46, n.4, abr, 2016.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 12 publications
(16 reference statements)
1
2
0
Order By: Relevance
“…Viscosity of ice cream can be affected by several factors, for example, composition; type and property of ingredients; processing and handling of mixture; total solid content; and temperature (Aranda-Gonzalez et al, 2016). In parallel with our results, Treciokiene and Sostakiene (2020) reported that the replacement of sugar with stevia or cherry puree affected the hardness of ice cream.…”
Section: Ta B L E 1 Effect Of Different Formulation On Physicochemical Properties Of Ice Creamsupporting
confidence: 88%
“…Viscosity of ice cream can be affected by several factors, for example, composition; type and property of ingredients; processing and handling of mixture; total solid content; and temperature (Aranda-Gonzalez et al, 2016). In parallel with our results, Treciokiene and Sostakiene (2020) reported that the replacement of sugar with stevia or cherry puree affected the hardness of ice cream.…”
Section: Ta B L E 1 Effect Of Different Formulation On Physicochemical Properties Of Ice Creamsupporting
confidence: 88%
“…S. rebaudiana is a naturally occurring calorie free sweetener that is also reported to have various medicinal benefits including antidiabetic, antihypotensive, antioxidant, anti-hyperglycemic, antibiotic and anticancerous agent without causing any detrimental side effects. [2][3][4][5][6] In terms of phytochemistry, S. rebaudiana are abundant sources of diterpenoids and diterpe-noid glycosides, [7][8][9][10] especially, stevioside, an entkaurene diterpenoid glycosides, which indicate a range of bioactivities including anti-inflammation, anti-cancer and immunomodulatory. [5,[11][12][13][14][15] In addition, it's essential to mention that these components are at least 200 times sweeter than sucrose, which is appropriate given its function as a natural sweetener.…”
Section: Introductionmentioning
confidence: 99%
“…And it is commercially grown in many parts of Central America, Brazil, Uruguay, Paraguay, Israel, Thailand and China but its cultivation has now become popular in various regions of the world. S. rebaudiana is a naturally occurring calorie free sweetener that is also reported to have various medicinal benefits including antidiabetic, antihypotensive, antioxidant, anti‐hyperglycemic, antibiotic and anticancerous agent without causing any detrimental side effects [2–6] . In terms of phytochemistry, S. rebaudiana are abundant sources of diterpenoids and diterpenoid glycosides, [7–10] especially, stevioside, an ent‐kaurene diterpenoid glycosides, which indicate a range of bioactivities including anti‐inflammation, anti‐cancer and immunomodulatory [5,11–15] .…”
Section: Introductionmentioning
confidence: 99%
“…A sacarose compõe entre 9 a 28%, os gelados comestíveis (FERRAZ, 2013;GOFF, 2018a;HARTEL, 2013a) GONZALEZ et al, 2016;OZDEMIR et al, 2015).…”
Section: Tendências E Inovações Na Produção De Sobremesas Congeladasunclassified